Oxidation and thermal shock resistance of TiAlCrY/YSZ thermal barrier coating on single-crystal TiAl alloys - Dijuan Han; Zhaopeng Tong; Xi Pan; Zhiyi Jin; Tianfang Sun; Yun Shen; Yaran Niu (Journal of Materials Research and Technology)
TiAl alloys are of significant interest due to their potential to replace nickel-based superalloys in aerospace applications. However, their limited oxidation resistance above 800 °C restricts their broader usage. In this study, we demonstrated that the antioxidant properties of a single-crystal TiAl alloy can be enhanced by depositing TiAlCrY/YSZ thermal barrier coating (TBC) using atmospheric/vacuum plasma spraying technology. The results showed that the oxide layer at the TiAlCrY/YSZ interface exhibited minimal spallation after oxidation at 1100 °C and 1200 °C for 200 h. Additionally, the spallation ratio of the YSZ coating was only about 2% after 200 thermal shock cycles at 1100 °C. These properties were comparable to those of the NiCrAlY/YSZ TBCs on nickel-based superalloys, suggesting excellent oxidation and thermal shock resistance. Microstructural analyses revealed that sufficient Al and favorable chemical compatibility at the coating/substrate interface contributed to the exceptional oxidation performance of the TiAlCrY bond coat. Furthermore, the well-matched thermal expansion coefficients (CTEs) among the TiAlCrY, YSZ coatings, and TiAl substrate provided excellent resistance to thermal shock. We believe our findings could offer valuable insights into the widespread application of TBCs on TiAl single crystals.